2007
DOI: 10.1002/hep.21661
|View full text |Cite
|
Sign up to set email alerts
|

The effects of discontinuing pioglitazone in patients with nonalcoholic steatohepatitis

Abstract: A pilot study of a 48-week course of pioglitazone demonstrated significant improvements in the biochemical and histological features of nonalcoholic steatohepatitis (NASH). The aim of the study was to assess the effects of stopping pioglitazone. Twenty-one patients with NASH were treated with pioglitazone (30 mg/day) for 48 weeks and underwent baseline and end-of-treatment evaluation including liver biopsy. Thirteen patients were followed for at least 48 weeks after stopping therapy and 9 underwent repeat live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
163
1
10

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(181 citation statements)
references
References 24 publications
7
163
1
10
Order By: Relevance
“…Further, growing evidence suggests that peroxisome proliferatoractivated receptors (PPARs) are implicated in NASHinduced fibrosis. Thus, PPAR-γ agonists ("glitazones") have been demonstrated to substantially improve liver histology in patients with NASH [36]. It remains to be determined whether ARB or PPAR-γ agonists are capable of affecting the profibrogenic effect of CM from steatotic hepatocytes, but regardless, we would like to propose the idea to study these and other questions in our in vitro model.…”
Section: Discussionmentioning
confidence: 99%
“…Further, growing evidence suggests that peroxisome proliferatoractivated receptors (PPARs) are implicated in NASHinduced fibrosis. Thus, PPAR-γ agonists ("glitazones") have been demonstrated to substantially improve liver histology in patients with NASH [36]. It remains to be determined whether ARB or PPAR-γ agonists are capable of affecting the profibrogenic effect of CM from steatotic hepatocytes, but regardless, we would like to propose the idea to study these and other questions in our in vitro model.…”
Section: Discussionmentioning
confidence: 99%
“…Steatohepatitis, which disappeared during treatment, recurred in most patients. 32 Fibrosis did not worsen, possibly because of the short follow-up. Sustained lifestyle modifications could prevent or delay histological relapse.…”
Section: Efficacy Outcomesmentioning
confidence: 93%
“…21 A reduction in serum-free fatty acid and a 1.9-to 2.8-fold increase in serum adiponectin were also documented with both glitazones. 21,22,32 Adiponectin increase reflects a strong improvement in hepatic IS, by as much as 48%. 22 Only one study showed no reduction in HOMA, only less deterioration in serum glucose or HbA1c levels.…”
Section: Efficacy Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…5 What should we make of the apparent divergent response in mice compared to humans and the limited positive response evident in the latter?…”
mentioning
confidence: 99%